2019
DOI: 10.1002/htj.21648
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis between two concentric rotating cylinders with heat and mass transfer

Abstract: The stability of the liquid/vapor interface between two concentric revolving cylinders is examined. The transfer of heat/mass is allowed at the interface. Both the cylinders rotate with different angular velocities. The fluids inside the annular region are taken as incompressible and viscous. The theory of viscous potential flow analysis is used to add the viscous effects. The normal mode technique is used to calculate the growth of perturbations. If we rotate the inner cylinder, it is seen that asymmetric dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This shows that MHT has a stabilizing influence. This outcome has been proven by several previous researchers; for instance, see Agarwal and Awasthi 49 .
Figure 13 The transition curve with the variation .
…”
Section: Nonlinear Stability Analysissupporting
confidence: 66%
“…This shows that MHT has a stabilizing influence. This outcome has been proven by several previous researchers; for instance, see Agarwal and Awasthi 49 .
Figure 13 The transition curve with the variation .
…”
Section: Nonlinear Stability Analysissupporting
confidence: 66%
“…[7] investigated the swirl impact on mass/heat transfer at the liquid-vapor interface. When both cylinders were rotating, the liquid-vapor interface in an annulus and studied its instability was considered [8]. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the system's instability is augmented when small Weber numbers are considered and gets suppressed at larger Weber numbers due to confinement. Lastly, Awasthi et al [13][14][15][16][17] scrutinized the stability of the various interfaces subject to heat and mass transfer between two concentric cylinders. They discovered that when the inner cylinder rotates, asymmetric disturbances destabilize the interface, whereas rotation of the outer cylinder induces stability.…”
Section: Introductionmentioning
confidence: 99%